Upamahādeśera samāja o pradhāna dvandva - Bala, Subrata (Subarṇarekhā, 1979)
On communist factionalism, chiefly in India and Bangladesh; analysis by a Naxalite leader in the context of the sociopolitical conditions of the Indian Subcontinent and Marxist ideology.